Applying tradable permits to biodiversity conservation: effects of space-dependent ecological benefits and cost heterogeneity on habitat allocation - Martin Drechsler; Frank Wätzold (Helmholtz-Zentrum für Umweltforschung (UFZ), 2007)
This paper is concerned with the cost-effective allocation of habitat for endangered species under spatio-temporally heterogeneous economic development. To address the dynamic dimension of the problem we consider tradable development rights (TDR) as the instrument of choice. A particular challenge in applying TDR is that the ecological benefit of an individual habitat patch depends on its spatial relationship with other habitats and thus is an emergent rather than a fixed property. We analyse the spatial and temporal dynamics of habitats in a region under a TDR market that takes spatial interaction of habitats explicitly into account. We show that depending on the levels of spatial interaction and cost heterogeneity, two different outcomes may emerge: an "ordered" structure where habitats are clustered in space and stable over time, and a "disordered" structure where habitats are scattered in space and subject to high turnover of destruction and recreation.
Keywords: Q24; Q28; Q57; 330; ecological-economic model; cost heterogeneity; phase transition; spatial interaction; tradable development rights; Biodiversität; Emissionsrechte; Räumliche Interaktion; Kosten-Wirksamkeits-Analyse; Theorie